Novel and Improved Crystal Structures of H. influenzae, E. coli and P. aeruginosa Penicillin-Binding Protein 3 (PBP3) and N. gonorrhoeae PBP2: Toward a Better Understanding of β-Lactam Target-Mediated Resistance. Issue 18 (23rd August 2019) - Bellini, Dom; Koekemoer, Lizbé; Newman, Hector; Dowson, Christopher G.
Abstract: Even with the emergence of antibiotic resistance, penicillin and the wider family of β-lactams have remained the single most important family of antibiotics. The periplasmic/extra-cytoplasmic targets of penicillin are a family of enzymes with a highly conserved catalytic activity involved in the final stage of bacterial cell wall (peptidoglycan) biosynthesis. Named after their ability to bind penicillin, rather than their catalytic activity, these key targets are called penicillin-binding proteins (PBPs). Resistance is predominantly mediated by reducing the target drug concentration via β-lactamases; however, naturally transformable bacteria have also acquired target-mediated resistance by inter-species recombination. Here we focus on structural based interpretations of amino acid alterations associated with the emergence of resistance within clinical isolates and include new PBP3 structures along with new, and improved, PBP-β-lactam co-structures. Graphical Abstract: Unlabelled Image Highlights: Historical perspective on penicillin-binding-protein (PBP) mediated resistance Focus upon amino acid alterations associated with PBP3 resistance New structural information and context of beta-lactam binding in relation to PBP3 mediated resistance